2017
DOI: 10.3389/fimmu.2017.00682
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Transcriptional and Alternative Splicing Signatures of Decidual CD4+ T Cells in Early Human Pregnancy

Abstract: Decidual CD4+ T (dCD4 T) cells are crucial for the maternal-fetal immune tolerance required for a healthy pregnancy outcome. However, their molecular and functional characteristics are not well elucidated. In this study, we performed the first analysis of transcriptional and alternative splicing (AS) landscapes for paired decidual and peripheral blood CD4+ T (pCD4 T) cells in human early pregnancy using high throughput mRNA sequencing. Our data showed that dCD4 T cells are endowed with a unique transcriptional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 85 publications
3
42
1
Order By: Relevance
“…Surface and intranuclear stainings were carried out by multicolor flow cytometry (FCM) as we and others described previously [34][35][36][37] . For cell surface staining, freshly isolated mononuclear cells were resuspended in 100 μL PBS containing 3% (v/v) fetal bovine serum (FBS) with different fluorescein-conjugated mAbs.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Surface and intranuclear stainings were carried out by multicolor flow cytometry (FCM) as we and others described previously [34][35][36][37] . For cell surface staining, freshly isolated mononuclear cells were resuspended in 100 μL PBS containing 3% (v/v) fetal bovine serum (FBS) with different fluorescein-conjugated mAbs.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Whether priming of the adaptive immune system occurs locally at the fetomaternal interface (in either the uterus or the placenta) remains unclear. Although maternal T and B cells populate both the uterine decidua 29,30 and the placenta (Lewis E, Sierra L-J, et al, in revision), studies of the uterine decidua during mouse pregnancy reveal that T cell trafficking into the decidua is limited. 31 Moreover, antigen presentation at the fetomaternal interface is quite altered compared to the secondary lymphoid organs, 32 and the human placental syncytiotrophoblast does not express classical HLA molecules that would promote T cell priming and differentiation.…”
Section: Fetal Alloantigen Disseminates Widely and Persists In Matementioning
confidence: 99%
“…Decidual T cells mainly include CD4+ helper T (Th) cells and CD8+ cytotoxic T cells. 1,22 Th1 and Th2 CD4 + T cells are found at the human maternal-fetal interface, and recurrent spontaneous abortion often correlates with an increased Th1/Th2 ratio. 1,23 However, few studies have clearly identified decidual macrophage subsets.…”
Section: Introductionmentioning
confidence: 99%